The Effect of Inflation and Gold Prices on the Performance of Gold Pawn Products at PT Bank Syariah Indonesia - Harahap, Febri Khairani; Sugianto; Nur Ahmadi Bi Rahmani (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2025)
This study aims to explain the effect of inflation and gold prices on the performance of gold pawn products at Bank Syariah Indonesia. The theory used in the research model is the performance theory. The data used in this study are secondary data obtained from the financial statements of Bank Syariah Indonesia, as well as macroeconomic data related to the inflation rate collected from Bank Indonesia and gold prices inputted from Antam via the official website. The results of the study indicate that inflation does not affect the performance of gold pawn products. Gold prices have a significant positive effect on the performance of gold pawn products at Bank Syariah Indonesia. Inflation and gold price data are collected monthly for the period 2021-2024. Furthermore, gold pawn performance data uses gold pawn distribution data (rahn) which is available in quarterly form and then converted into monthly data using the linear interpolation method.